Politisasi Anggaran Bantuan Keuangan oleh Petahana pada Pilkada Serentak di Indonesia - Sinaga, Austin Nalsalina (UI Scholars Hub, 2025)
This study aims to inquire the Political Budget Cycle (PBC) by examining the relationship between the presence of an incumbent during the simultaneous district/city level elections in 2015, 2017, 2018, 2020 and village financial assistant. Using the village financial assistant data in 2013-2021, this study conducts a random effect model. The results showed that the existence of an incumbent is significantly correlated with an increase in village financial assistant in one or two years prior to election. Meanwhile, in the election year, there is no significant relationship between variables. The PBC took place in the years prior to election.